THE USE OF E-MONEY IN STATE OWNED BANKS IN MANADO - Lestari, Novi Dwi; Lambey, Linda .; Tumiwa, Johan . (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: The advanced payment system has shifted the role of cash as a means of payment to the form of non-cash payment to be more efficient and economical. In Indonesia there are 10 banking sectors that have obtained permission from Bank Indonesia and in Manado E-money product that comes from State-owned banks are the most popular in the society, which are: BRIZZI from BRI, Tapcash from BNI, E-cash and E-money from Mandiri bank. The purpose of this research is to analyze the actual usage and the preferences of electronic money users by State-owned banks in Manado. This study uses descriptive qualitative research to describe the customerâ€™s perception and their preferences by using E-money in State-owned banks in Manado from 22 informants by used semi in- depth interviews. The result of the research shows that E-money users from State-owned banks in Manado have received and used electronic money as a means of payment. However, the volume of transactions in using E-money is insufficient due to the lack of supported payment facilities. The e-money users have the same preference in using e-money because it is easy to use and many promotions are given. The E-money issuer prefer to develop the infrastructure to support E-money payment.Â Keywords: e-money and state-owned bank Â